Sistem Ketatanegaraan Indonesia Pasca Amandemen UUD 1945 - Warjiati, Sri (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2012)
Abstract: The article discuss the changes of indonesian political system in indonesia after the amendment of Indonesian Constitution of 1945 with the focus of the amendments of legislative, eecutive and judicative bodies. Legislative amendments is located in the emergence of a new body called DPD (Dewan Perwakilan Daerah of Regional Representative Assembly) as a part of MPR (Majelis Permusyawaratan Rakyat or People’s Consulatation Assembly) alongside DPR (Dewan Perwakilan Rakyat or House of Representative). Such amendment is basically a modifictaion of bicameral system as that of the United States’ political system. Executive body amendments lies on direct election of president, limitation of presidential tenure up to two tenures of five years, and likeliness of presidential impeachment in case of breaking law and constitution. Amendment on judicative body is obviously apparent in the creation of Constitutional Court alongside the Supreme Court and Judicial comission which is in charge of safeguarding the judgeship profession. Kata Kunci: Amandemen, UUD, dan System Ketatanegaraan